Kajian Sifat Mekanik Beban Kejut Komposit Epoksi Berpenguat Serat Sabut Kelapa - Indra Mawardi; Zul Saputra; Fakhriza - (Politeknik Negeri Lhokseumawe, 2017)
This study aims to determine the impact strength fiber-reinforced epoxy composites coco Composites made using a matrix of fiber-reinforced epoxy resin and coco. Coco fiber used is cleaned and dried in the sun for three days. Coco fiber is cut with every fiber length ± 3 cm, then soaked in an alkaline solution (NaOH) 2.5% for 5 hours. Composites formed with a variation of the weight of the matrix of the fiber that is 10, 20, and 30. This experiment is testing the impact. The highest impact toughness value generated on epoxy composite with the addition of coconut coir fiber as much as 30% compared to 20 and 10% variation. The greater the percentage of coco fiber, the higher the value of the impact toughness